2014
DOI: 10.1158/1535-7163.mct-14-0183
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Catabolism via CPT1 as a Therapeutic Target for Prostate Cancer

Abstract: Prostate cancer (PCa) is the most commonly diagnosed malignancy among western men and accounts for the second leading cause of cancer-related deaths. PCa tends to grow slowly and recent studies suggest that it relies on lipid fuel more than on aerobic glycolysis. However, the biochemical mechanisms governing the relationships between lipid synthesis, lipid utilization, and cancer growth remain unknown. To address the role of lipid metabolism in PCa we have used Etomoxir and Orlistat, clinically safe drugs that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
240
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(257 citation statements)
references
References 50 publications
16
240
0
1
Order By: Relevance
“…Moreover, the short chain fatty acids, which then are released from the peroxisome might further fuel the TCA cycle by their full β-oxidation in the mitochondria. Although enzymes of mitochondrial β-oxidation are not increased in prostate cancer [140], it has been shown that etomoxir-mediated inhibition of mitochondrial β-oxidation at the level of carnitine palmitoyltransferase 1 induces cell death in prostate cancer cell lines [143]. Interestingly, prostate cancer also induces fatty acid biosynthesis by overexpressing fatty acid synthase early during tumor progression without lipid accumulation [144,145], which is further consistent with 11 C-acetate PET/CT experiments [146].…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, the short chain fatty acids, which then are released from the peroxisome might further fuel the TCA cycle by their full β-oxidation in the mitochondria. Although enzymes of mitochondrial β-oxidation are not increased in prostate cancer [140], it has been shown that etomoxir-mediated inhibition of mitochondrial β-oxidation at the level of carnitine palmitoyltransferase 1 induces cell death in prostate cancer cell lines [143]. Interestingly, prostate cancer also induces fatty acid biosynthesis by overexpressing fatty acid synthase early during tumor progression without lipid accumulation [144,145], which is further consistent with 11 C-acetate PET/CT experiments [146].…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 56%
“…Moreover, inhibition of fatty acid biosynthesis and oxidation was reported to inhibit tumor growth [143,148,149]. Yet, cancer cell lines, such as DU-145, LNCaP and PC-3 exhibit an elevated fatty acid uptake from the environment, which renders them less sensitive to inhibition of fatty acid biosynthesis [150][151][152].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…During transformation to early lesions, prostate cancer cells progressively switch toward OXPHOS-dependent metabolism (47). Interestingly, prostate cancer cells prioritize glycolytic metabolism during late stages of cancer progression, rendering them sensitive to 2-DG (13,(48)(49)(50)(51)(52)(53)(54). Thus, prostate cancer cells exhibit a mixed phenotype, where both glycolysis and OXPHOS are required for energy metabolism at different stage of disease progression (Table 1; ref.…”
Section: Metabolic Heterogeneity Between Tumor Typesmentioning
confidence: 99%
“…FAO is activated in several type of cancers, and the transcription factor, PPARa, is the main regulator of this process (80)(81)(82)(83). PPARa can be activated by endogenous fatty acid, fatty acid derivatives or fibrates, and is coregulated by PGC1a (84,85).…”
Section: Pml/pgc1a/ppara Axis In Breast Cancermentioning
confidence: 99%